1988
DOI: 10.1002/1097-4679(198807)44:4<516::aid-jclp2270440407>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The depression coping questionnaire

Abstract: Factor analysis of the Depression Coping Questionnaire (DCQ; Kleinke, Staneski, & Mason, 1982) identified 11 coping responses: Social support, problem solving, self‐blame/escape, aggression, indulgence, activities, medication, stimulation, eating, TV, and ignoring. Multiple regression analyses indicated that the DCQ contributed significant variance in predicting Beck Depression Inventory (BDI) scores of men (R = 0.705) and women (R = 0.568) from three population samples. Both men's and women's BDI scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Sedentary behavior was measured using various methods. For example, TV viewing was measured using time-use logs [40] and questionnaires [51,52]; computer/internet use was measured using computer software [48,53] and questionnaires [39,42]; overall sedentary behavior (i.e., sitting and lying time) was measured using a "Sedentary Index" [41], as well as by more direct measures such as accelerometers [54]. These measures are described in further detail in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sedentary behavior was measured using various methods. For example, TV viewing was measured using time-use logs [40] and questionnaires [51,52]; computer/internet use was measured using computer software [48,53] and questionnaires [39,42]; overall sedentary behavior (i.e., sitting and lying time) was measured using a "Sedentary Index" [41], as well as by more direct measures such as accelerometers [54]. These measures are described in further detail in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 studies, seven (six observational and one intervention) found a positive association between sedentary behaviors and risk of depression [39][40][41][51][52][53][54]. A total of two intervention studies found an inverse association between sedentary behavior and risk of depression (i.e., the greater time spent in sedentary behavior, the lower the odds of depressive symptoms) [48,55].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations